COUNSELING ON THE USE OF FAMILY MEDICINAL PLANTS (TOGA) - WERDININGSIH, WIWIK WERDININGSIH (Institut Ilmu Kesehatah Bhakti Wiyata Kediri, 2024)
Dadapan Village is an urban area but is categorized as a disadvantaged village because its location is quite far from the center of Kediri city, so this hamlet is a hamlet that can be categorized as a rural area. Most of the people in Dadapan hamlet are housewives. The area of Dadapan hamlet is quite large and not too dense, so there are still many large yards in the hamlet. Residents in Dadapan hamlet are used to using the yards around their houses to plant various types of plants. Of the various kinds of plants that live in people's yards, many of them are plants that can be used as traditional medicinal plants. Some residents sometimes use these plants to treat health complaints, but their use is not optimal because so far the use of traditional medicinal plants has only been based on the opinions of friends or neighbors. It is feared that the use of traditional medicines that do not comply with the rules could reduce the efficacy of the medicine itself. If it is used too much, it is feared that it will also have toxic effects that will harm society. By using the method of educating the public about the TOGA utilization program at the PKK meeting on Sunday 14 January 2024, it is hoped that it will provide the public with insight into the use of TOGA to be managed into medicinal preparations to improve family health. The results of the posttest showed that 100% of the community understood and could explain the use of TOGA for family health.